Ebola virus disease – gaps in knowledge and practice among healthcare workers in Lagos, August 2014. Issue 9 (1st June 2015) - Oladimeji, Abisola M.; Gidado, Saheed; Nguku, Patrick; Nwangwu, Iruoma Genevieve; Patil, Nikhil D.; Oladosu, Femi; Roberts, Alero Ann; Waziri, Ndadilnasiya E.; Shuaib, Faisal; Oguntimehin, Olukayode; Musa, Emmanuel; Nasidi, Abdulsalami; et al.
Abstract Objective Healthcare workers (HCWs) play pivotal roles in outbreak responses. Ebola virus disease (EVD) outbreak spread to Lagos, Nigeria, in July 2014, infecting 11 HCWs (case fatality rate of 45%). This study was conducted during the outbreak to assess HCWs' EVD‐related knowledge and practices. Methods A health facility‐based cross‐sectional study was conducted among HCWs across Lagos State using stratified sampling technique. An interviewer‐administered questionnaire was administered to elicit respondents' socio‐demographic characteristics, knowledge and practices. A checklist assessing health facility's level of preparedness and HCWs' EVD‐related training was employed. HCWs' knowledge and practices were scored and classified as either good or poor. Multivariate analysis was performed with confidence interval set at 95%. Results A total of 112 health facilities with 637 HCWs were recruited. Mean age of respondents was 40.1 ± 10.9 years. Overall, 72.5% had good knowledge; doctors knew most. However, only 4.6% of HCWs reported good practices. 16.6% reported having been trained in identifying suspected EVD patient(s); 12.2% had a triaging area for febrile patients in their facilities. Higher proportions of HCWs with good knowledge and training reported good practices. HCWs with EVD‐related training were three times more likely to adopt good practices. Conclusion Lagos State HCWs had good knowledge of EVD without a corresponding level of good practices. Training was a predictor of good practices.